Evaluation of a liaison librarian program: client and liaison perspectives. - Tennant MR; Tobin Cataldo T; Sherwill-Navarro P; Jesano R (Journal of the Medical Library Association, 2006)
OBJECTIVES: This paper describes a survey-based evaluation of the five-year old Liaison Librarian Program at the University of Florida. METHODS: Liaison librarians, faculty, students, staff, residents, and post-doctoral associates were queried via Web-based surveys. Questions addressed client and liaison perspectives on a variety of issues, including program and service awareness and usage, client-library relations and communication, client support for the program, and liaison workload. RESULTS: Approximately 43% of the 323 client respondents were aware of liaison services; 72% (n = 163) of these clients had had contact with their liaison. Ninety-five percent (n = 101) of faculty and students who reported contact with their liaison supported the continuation of the program. Liaison services were used by a greater percentage of faculty than students, although they had similar patterns of usage and reported the same 'traditional' services to be most important. Liaisons indicated that communications with clients had increased, the reputation of the library was enhanced, and their workloads had increased as a result of the Liaison Librarian Program. CONCLUSIONS AND RECOMMENDATIONS: Survey results suggest that the Liaison Librarian Program has a core set of clients who use and highly value the services provided by liaisons. Recommendations addressing workload, training, marketing, and administrative support are provided.